Lower limb rehabilitation using modified constraint-induced movement therapy and motor relearning program on balance and gait in sub-acute hemiplegic stroke: a comparative study [version 1; peer review: awaiting peer review] - Chavan, Nitika S.; Raghuveer, Raghumahanti (F1000 research, 2023)
Background: A stroke is described by the World Health Organization as "a clinical syndrome with rapidly developing symptoms that consist of a focal (or global, in a situation of coma) disruption of cerebral function that lasts more than 24 hours or leads to mortality without a known cause other than a vascular origin". Stroke is the most prevalent cause of impairment and mortality on a global scale. Modified constraint-induced movement therapy (mCIMT) is an approach to therapy for motor disabilities that involves constraining the movements of the nonparetic limb, diligent practice and behaviour modification to extend the time the paretic limb is utilized for daily tasks. The motor relearning program (MRP) method involves many aspects of motor learning theory and is helpful in providing instructions for retraining practical skills (including walking, standing and sitting in balance and transferring abilities). So, the objective of this study is to assess the impact of the MRP and mCIMT on balance and gait in sub-acute hemiplegic stroke patients. Methods: In this study, each group will consist of 17 people in total. The randomization procedure will be conducted using a computer-generated random number system. For sample distribution, we will use the sequentially numbered opaque sealed envelope technique. Outcome measures will be as follows: Berg balance scale, Dynamic gait index, Trunk impairment scale, Functional reach test, 10 Meter walk test and Fall efficacy test. Each patient will be evaluated prior to and during treatment at baseline and six weeks later. Conclusions: There is sufficient evidence to derive the conclusion that the functional mobility and balance of stroke victims can be improved with physiotherapy. Therefore, this study will try to seek the comparison of mCIMT and MRP in sub-acute stroke subjects and compare the two regimes to determine which one will be superior. Registration: CTRI ( CTRI/2023/05/052674; 16/05/2023).